Evaluation of therapeutic efficacy of anticoagulant drugs for patients with venous thromboembolism during pregnancy: A systematic review and meta-analysis. (July 2019) - Chen, Guo-Chang; Gao, Hong; Zhang, Lin; Tong, Tong
Abstract: A meta-analysis based on published literature was undertaken to evaluate the efficacy of anticoagulant drugs for the treatment of venous thromboembolism during pregnancy. PubMed, Cochrane and Embase databases were searched from inception to September 2018 for relevant studies using indexed words, including qualified case–control and cohort studies. The meta-analysis used odds ratios (OR) and 95% confidence intervals (95% CI) to analyse the primary results. Nine studies were included in this meta-analysis, with a total of 834 cases and 3424 controls. There were no significant differences in the incidence of prenatal haemorrhage (OR 1.08, 95% CI 0.84–1.40), venous thromboembolism (OR 1.30, 95% CI 0.72–2.33) or caesarean section (OR 1.16, 95% CI 0.69–1.98) between the case group and the control group. The incidence of pulmonary embolism was significantly higher in the case group than in the control group (OR 3.90, 95% CI 1.23–12.34). However, there were a few limitations that may have influenced the results, so more randomized double-blind controlled studies of high quality are warranted to confirm the efficacy of anticoagulant therapy for venous thromboembolism in pregnancy.